The Complete guide to dream kitchens. - 4 0 16; 5 (Chanhassen, Minnesota : Creative Publishing International, Inc., 2007)
Shows homeowners what's hot and what's not, and gives practical information on how they can achieve the kitchens of their fantasies. Recent innovations in planning and room layout are covered in detail, and the merits of premium building materials and appliances are discussed and compared. Also gives many actual how-to projects for creating luxury kitchens with professional results--Provided by publisher.
Includes index.;At head of title: Black & Decker.
Keywords: 2 -- 0; 6; Remodeling. -- Kitchens -- 20; 20; 2